PEMBIAYAAN MUDHARABAH, RISIKO, DAN PENANGANANNYA (Studi Kasus pada Bank BTN Kantor Cabang Syariah Malang) - ., Friyanto (Jurnal Manajemen dan Kewirausahaan, 2013)
Mudharabah is a cooperation between two or more parties, in which the owner of the capital entrusts the manager, amount of capital with profit-sharing agreement. The faced risks are information asymmetry and moral hazard. The purposes of this study were to minimize the risks and understand the solutions. This research used problem solving method. The research object was BTN Syariah Malang Branch. The result of this study indicated that the risks can be minimized by determining specific conditions that must be obeyed.